2001
DOI: 10.4314/jfta.v6i3.19297
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and Rheological evaluation of West African Soft cheese made from plant coagulant (Calotropis procera) during storage

Abstract: Storage of West African soft cheese "Warankasi" for up to 15 weeks in a refrigerator was examined for the composition, protein fractions (non casein nitrogen, non protein nitrogen, casein nitrogen, total nitrogen) hardness, cohesiveness, gumminess, elasticity, chewiness, adhesiveness and pH. Whereas cheese hardness, gumminess, elasticity, chewiness and adhesiveness decreased as the storage day progressed, the protein fractions (NCN, NPN, CN, and total nitrogen) increased slightly. Each of the textural measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
3
1
0
Order By: Relevance
“…Street-vended warankasi content (%) of warankasi samples (Table I) was in the range of 1.31±0.03-1.86±0.09. These results and ranges are for the 8 different markets analyzed and similar to the findings of Alalade and Adeneye (2006) and Belewu (2001). The warankasi samples have high amount of protein and fat contents and this agreed with the work of Belewu (2001).…”
supporting
confidence: 89%
See 2 more Smart Citations
“…Street-vended warankasi content (%) of warankasi samples (Table I) was in the range of 1.31±0.03-1.86±0.09. These results and ranges are for the 8 different markets analyzed and similar to the findings of Alalade and Adeneye (2006) and Belewu (2001). The warankasi samples have high amount of protein and fat contents and this agreed with the work of Belewu (2001).…”
supporting
confidence: 89%
“…The results of quality indices for the eight different markets analyzed revealed that the TSN (mgN/kg) and the VFA (%) of warankasi samples (Table II) were in the range of 1.19 ± 0.10-2.54 ± 0.18 and 5.79 ± 0.19-9.12 ± 0.30, respectively. These results and ranges were in the ranges reported by Alalade and Adeneye (2006) and Belewu (2001).TSN is related to protein breakdown and is an index of milk spoilage. The legislative standard for TSN include: 20 mgN/100 g for fresh milk and dairy products.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…The results obtained are as presented in Tables 1 and 2. The results of the proximate and mineral analyses showed differences in fat, protein, moisture, carbohydrate ash and calcium contents of Calotropis procera, Moringa oleifera and lemon juice coagulated cheeses. Out of the six samples prepared, Calotropis procera yielded highest value (64.50%) of fat content, which is higher than the value (31.45%) reported by Belewu, 2001, Johnson et al 2001. The higher fat content in Calotropis Procera cheese could be as a result of its high coagulating strength.…”
Section: Resultsmentioning
confidence: 64%